Immunotherapy of melanoma - Bender, Carolin; Hassel, Jessica C.; Enk, Alexander (Oncology research and treatment, 2016)
Arising from melanocytes in skin, mucosal membranes, eye, and meninges, melanoma is a tumor that has been associated with poor prognosis in advanced disease stages. Given the poor response to chemotherapy and radiation therapy, new treatment approaches with targeted therapy, immunotherapy, and adoptive T-cell therapy have revolutionized the standard of care for patients with advanced melanoma. This review provides a short overview of past, present, and future immunotherapeutic approaches and their limitations, with a focus on new combination agents in early clinical trials.
Gesehen am 16.08.2019